Experimental Designs to Study the Aggregation and Colonization of Biofilms by Video Microscopy With Statistical Confidence - Pettygrove, Brian A.; Smith, Heidi J.; Pallister, Kyler B.; Voyich, Jovanka M.; Stewart, Philip S.; Parker, Albert E. (Frontiers in Microbiology, 2022)
The goal of this study was to develop a statistical assessment of confocal laser scanning microscopy (CLSM) time-lapse images of early colonizing biofilms to quantify the variability of imaging data to aid in the design of future imaging experiments. To accomplish this a large imaging dataset consisting of 16 independent CLSM microscopy experiments was leveraged. These experiments were designed to study interactions between human neutrophils and single cells or aggregates of Staphylococcus aureus (S. aureus) during the initial stages of biofilm formation. Results suggest that in untreated control experiments, variability differed substantially between growth phases (i.e., lag or exponential). When studying the effect of an antimicrobial treatment (in this case, neutrophil challenge), regardless of the inoculation level or of growth phase, variability changed as a frown-shaped function of treatment efficacy (i.e., the reduction in biofilm surface coverage). These findings were used to predict the best experimental designs for future imaging studies of early biofilms by considering differing i.) numbers of independent experiments; ii.) numbers of fields of view (FOV) per experiment; and iii.) frame capture rates per hour. A spreadsheet capable of assessing any user-specified design (i.e., number of experiments, FOVs and number of images over time) is included that requires the expected mean log reduction and variance components from user-generated experimental results. The methodology outlined in this study can assist researchers in designing their CLSM studies of antimicrobial treatments with a high level of statistical confidence.